2018
DOI: 10.1002/gps.4907
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Adolescent Attitudes towards Dementia Scale (A‐ADS)

Abstract: The scale will allow the evaluation of educational initiatives for young people and provide a validated and standardised measure to establish adolescents' attitudes towards dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The Adolescent Attitudes towards Dementia Scale (AADS [18];) is a 23-item validated measure of attitudes and knowledge of dementia, designed for use with adolescents. The measure covers 3 subdomains; perceptions of dementia, personal sacrifice, and empathy with people living with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…The Adolescent Attitudes towards Dementia Scale (AADS [18];) is a 23-item validated measure of attitudes and knowledge of dementia, designed for use with adolescents. The measure covers 3 subdomains; perceptions of dementia, personal sacrifice, and empathy with people living with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…The A-ADS (Griffiths et al, 2018) is a 23 item scale that captures attitudes towards dementia in adolescents. Items are rated on a 5 point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Estimation. Two models were created 1) using the three factor structure described in Griffiths et al, (2018), and 2) using the factor structure of the 13-item A-ADS identified in the EFA.…”
Section: Cfa: a Structural Equation Model Was Created (Amos) Using Mamentioning
confidence: 99%
“…Adolescents' perceptions of dementia were captured through the Adolescent Attitudes towards Dementia Scale (A-ADS) (Griffiths, Parveen, Shafiq, & Oyebode, 2018). The A-ADS is a 23item measure of dementia attitudes and knowledge of dementia in adolescents, capturing "perceptions of dementia", "empathy towards people with dementia", and "personal sacrifice".…”
Section: Methodsmentioning
confidence: 99%